2015
DOI: 10.2319/040314-245.1
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two different mandibular advancement devices on craniofacial characteristics and upper airway dimensions of Chinese adult obstructive sleep apnea patients

Abstract: Monoblock was the better MAD to improve OSA severity. No difference could be found in changes of subjective OSA indicators. Significant but similar cephalometric changes were observed, indicating both MADs alter the position of the surrounding musculature and improve upper airway patency. Therefore, the different design features of the MADs suggest an impact on some OSA indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…Zhou and Liu (2012) demonstrated different results with a monoblock versus twin-block appliance using the same jaw position during a single-night titration study. Similar interesting results have been reported in comparison studies of two different MADs (Geoghegan et al 2015;Isacsson et al 2016). Geoghegan et al (2015) evaluated the effects of two different MADs (monoblock and twinblock) with the same bite registration as used in the study by Zhou and Liu (2012) and found that monoblock appliances reduced the AHI more than twin-block appliances.…”
Section: Titration Proceduressupporting
confidence: 77%
See 1 more Smart Citation
“…Zhou and Liu (2012) demonstrated different results with a monoblock versus twin-block appliance using the same jaw position during a single-night titration study. Similar interesting results have been reported in comparison studies of two different MADs (Geoghegan et al 2015;Isacsson et al 2016). Geoghegan et al (2015) evaluated the effects of two different MADs (monoblock and twinblock) with the same bite registration as used in the study by Zhou and Liu (2012) and found that monoblock appliances reduced the AHI more than twin-block appliances.…”
Section: Titration Proceduressupporting
confidence: 77%
“…Similar interesting results have been reported in comparison studies of two different MADs (Geoghegan et al 2015;Isacsson et al 2016). Geoghegan et al (2015) evaluated the effects of two different MADs (monoblock and twinblock) with the same bite registration as used in the study by Zhou and Liu (2012) and found that monoblock appliances reduced the AHI more than twin-block appliances. Conversely, in another study comparing monoblock and twin-block appliances, Isacsson et al (2016) reported that both types significantly reduced the AHI and sleepiness to the same degree.…”
Section: Titration Proceduressupporting
confidence: 77%
“…The wide variability in the reported treatment efficacy of MSAs for OSA may be attributable to the wide variety of available designs . However, few studies have compared the efficacy between adjustable MASs allowing mouth opening and fixed MASs that maintain mouth closure . Mouth opening during sleep tends to induce backward movement of the mandible, tongue, and soft palate, which in turn narrow the oropharyngeal airspace .…”
Section: Discussionmentioning
confidence: 69%
“…Studies have compared fixed with twin‐block MAS designs . Bloch et al reported no difference in the reduction in AHI achieved with the two MAS types .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation